The effects of pharmaceutically active compound doxycycline on the corrosion of mild steel in hydrochloric acid solution - Shukla S.K.; Quraishi M.A. (My University, 2025)
Corrosion inhibition of mild steel in hydrochloric acid solution by doxycycline has been studied by weight loss measurements, polarization resistance, Tafel polarization and electrochemical impedance spectroscopy. The inhibitor showed more than 95% inhibition efficiency at optimum concentration 9.02 × 10-4 M. Potentiodynamic polarization suggests that it is a mixed type of inhibitor. Electrochemical impedance spectroscopy was used to investigate the mechanism of corrosion inhibition. Thermodynamic parameters were calculated to investigate mechanism of inhibition. The compound follows Langmuir adsorption isotherm. AFM studies of mild steel surface with and without inhibitor were performed and calculated roughness also supported the inhibition data. © 2009 Elsevier Ltd. All rights reserved.